Deep Learning for Beginners: A Beginner's Guide to Getting up and Running with Deep Learning from Scratch Using Python - Rivas, Pablo (Packt Publishing, Limited, 2020)
This book is for beginners who are looking for a strong foundation to build deep learning models from scratch. You will test your understanding of the concepts and measure your progress at the end of each chapter. You will have a firm understanding of deep learning and will be able to identify which algorithms are appropriate for different tasks.